2022
DOI: 10.1162/nol_a_00048
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual Combination in the LATL With and Without Syntactic Composition

Abstract: The relationship between syntactic, semantic, and conceptual processes in language comprehension is a central question to the neurobiology of language. Several studies have suggested that conceptual combination in particular can be localized to the left anterior temporal lobe (LATL), while syntactic processes are more often associated with the posterior temporal lobe or inferior frontal gyrus. However, LATL activity can also correlate with syntactic computations, particularly in narrative comprehension. Here w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 62 publications
2
12
0
Order By: Relevance
“…Even though the brain is sensitive to local phrase structure in composition (Mollica et al, 2020), we have shown that two lexical items that are part of separate syntactic phrases can engage the LATL in a very similar way to how those two words would if they were part of the same phrase. This extends previous findings from Parrish and Pylkkänen (2022) which showed that the LATL is engaged in conceptual combination for two words that do not syntactically merge (but are otherwise part of the same DP structure). This study furthers our understanding of how conceptual combination fits in to a larger parsing model as well as narrowing down the possibilities of how the mechanism behind conceptual combination operates.…”
Section: Implications For Conceptual Combinationsupporting
confidence: 89%
See 2 more Smart Citations
“…Even though the brain is sensitive to local phrase structure in composition (Mollica et al, 2020), we have shown that two lexical items that are part of separate syntactic phrases can engage the LATL in a very similar way to how those two words would if they were part of the same phrase. This extends previous findings from Parrish and Pylkkänen (2022) which showed that the LATL is engaged in conceptual combination for two words that do not syntactically merge (but are otherwise part of the same DP structure). This study furthers our understanding of how conceptual combination fits in to a larger parsing model as well as narrowing down the possibilities of how the mechanism behind conceptual combination operates.…”
Section: Implications For Conceptual Combinationsupporting
confidence: 89%
“…The copyright holder for this preprint this version posted December 13, 2022. ; https://doi.org/10.1101/2022.12.11.519989 doi: bioRxiv preprint Running head: NON-LOCAL CONCEPTUAL COMBINATION 6 in the syntax (Parrish & Pylkkänen, 2022). The current study tests if such syntax-independent composition can occur across a long distance.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…In parallel to identifying the lexical-semantic representations of adjectives, we showed that negation is significantly decodable at each modifier’s presentation time (reflecting word form encoding and semantic encoding), and its decodability remains sustained throughout the presentation of the adjective, up to ∼700 ms (see Zhang and Pylkkänen, 2018 for a similar result at the sentence level). This pattern was mainly observed in phrases with two modifiers, likely reflecting syntactic and semantic compositional processes (Fedorenko et al, 2016; Pallier et al, 2011; Parrish and Pylkkänen, 2022). These results demonstrate that the lexical-semantic features of adjective and negation are processed in a parallel fashion, as opposed to serially (see Fyshe et al, 2019 for a similar pattern for adjective and noun in the context of adjective-noun phrases).…”
Section: Discussionmentioning
confidence: 93%
“…Cumulatively, these results suggest that the brain encodes negation every time a "not" is presented and maintains this information up to 720 ms after adjective onset. Further, they show that the duration of negation maintenance is amplified by the presence of a second modifier (i.e., "really"), highlighting combinatoric effects [2,6,50].…”
Section: ) Temporal Decoding Of Antonyms and Negationmentioning
confidence: 99%